Compound containing single-layer graphene oxide as well as preparation method and application of compound
The single-layer graphene oxide composite was prepared by ball milling and combined with gas induction agent and water-soluble filler, which solved the problems of poor dispersion and limited freeze-thaw resistance in concrete, significantly improving the integration of cement-based materials performance.
Patent Information
- Application Number
- CN202411635431.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-14
AI Technical Summary
Graphene oxide has poor dispersion in concrete, which affects its application performance, and has limited resistance to freeze-thaw when used alone.
A single layer of graphene oxide composite was prepared by ball milling and combined with a gas induction agent and a water-soluble filler, and applied as an additive in cement-based materials.
The dispersion of graphene oxide in cement-based materials has been improved, and the freeze-thaw resistance, compressive strength, permeability and ease of concrete have been significantly improved.
Smart Images

Figure CN119430712A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a composite material containing a single-layer graphene oxide, and a preparation method and application thereof. Background Art
[0002] As a new type of two-dimensional nanomaterial, graphene oxide has potential application value in concrete; it can be compounded with polycarboxylate water-reducing agent and applied to cement-based materials to improve the compression resistance, crack resistance and impermeability of cement-based materials. However, when graphene oxide is used alone, the degree of improvement in freeze-thaw resistance is limited, and the freeze resistance grade is usually less than F300. In addition, graphene oxide will reduce the workability and slump of concrete, affecting the application performance.
[0003] Traditionally, graphene oxide is mainly prepared by chemical methods. The graphene oxide precursor is washed and ultrasonicated to obtain graphene oxide. The graphene oxide prepared by this method has poor dispersibility in concrete and needs to be compounded with polycarboxylic acid water reducer when used, which increases the inconvenience of application.
[0004] Based on the above problems, a method for preparing graphene oxide composites by ball milling is proposed, and the prepared product is compounded with an air entraining agent and applied as an additive in cement-based materials. Summary of the invention
[0005] The purpose of the present invention is to provide a composite containing a single-layer graphene oxide and a preparation method and application thereof, so as to solve the problems in the background technology.
[0006] To achieve the above object, the present invention provides a method for preparing a composite containing a single-layer graphene oxide, the steps of which are as follows: The graphene oxide precursor is washed with water and ultrasonicated, the formed slurry is ball-milled, and building material powder is added during the ball-milling process to obtain a composite formed by a single layer of graphene attached to the surface of the powder.
[0007] Preferably, the building material powder is one of fly ash, recycled aggregate and slag powder.
[0008] Preferably, in the composite, the mass ratio of graphene oxide to building material powder is 5:1 to 50:1.
[0009] The present invention also provides a composite material containing a single-layer graphene oxide, which is prepared by the above-mentioned preparation method.
[0010] The present invention also provides an application of a composite material containing a single layer of graphene oxide, and the prepared composite material is applied as an additive in cement-based materials.
[0011] Preferably, the additives further include air entraining agents and water-soluble fillers.
[0012] Preferably, the additive is prepared by adding a composite containing a single-layer graphene oxide to an aqueous solution of an air entraining agent, stirring evenly, and then adding a water-soluble filler to obtain an additive for a cement-based material; Alternatively, an air entraining agent and a water-soluble filler are added during the ball milling process of preparing a composite containing a single-layer graphene oxide, and finally an additive for a cement-based material is obtained.
[0013] Preferably, in the additive of the cement-based material, the mass ratio of the air entraining agent to the graphene oxide is 5:1-50:1, and the ratio of the water-soluble filler to the graphene oxide is 2:1-20:1.
[0014] Preferably, the air entraining agent is an anionic surfactant, and the air entraining agent is one of sodium rosin acid, modified rosin sulfonate, alkyl sulfonic acid / sulfate, and fatty acid salt; and the water-soluble filler is silica sol.
[0015] Therefore, the present invention discloses a composite containing a single-layer graphene oxide and a preparation method and application thereof, which have the following beneficial effects: (1) In the application of cement-based materials, the traditional method is to use polycarboxylic acid water-reducing agent to improve the dispersion state of graphene oxide in concrete; however, in the present invention, the obtained graphene oxide precursor is ball-milled, and fly ash, recycled aggregate, slag powder and other powders are added during the ball-milling process. These powders not only help to improve the graphene monolayer rate, but also the formed graphene flake structure is tightly attached to the surface of the powder, which is conducive to the dispersion of graphene in cement-based materials, thereby improving its application performance.
[0016] (2) In the present invention, an air entraining agent, a water-soluble filler and graphene oxide ball-milled with fly ash are compounded to obtain a water-based composite additive, which is added to cement-based materials to improve the performance of cement-based materials. Among them, the air entraining agent can improve the freeze-thaw resistance of cement-based materials; the water-soluble filler can be filled into micropores, reduce volume shrinkage, and improve impermeability; after ball milling, the dispersibility of the single-layer graphene oxide attached to the surface of the powder is improved, which can improve the workability of the cement-based material. From the perspective of the use effect, while significantly improving the freeze-thaw resistance, the mechanical properties such as compressive strength are maintained.
[0017] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The BET characterization diagram of the products of Example 1 and Comparative Example 1 of the present invention, wherein 1 # Representative Examples 1, 2 # Representative comparative examples 1, 3 #Representative fly ash was ball milled at 300 r / min for 12 h. DETAILED DESCRIPTION
[0019] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0020] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.
[0021] Example 1 The graphene oxide precursor obtained by electrochemical treatment was washed with water and ultrasonicated for 12 min. The formed slurry was ball milled, and fly ash was added during the ball milling process. The mass ratio of fly ash to graphene oxide was 10:1. The ball milling time was controlled to be 13 h and the ball milling speed was 300 r / min to obtain a composite containing a single-layer graphene oxide.
[0022] Comparative Example 1 The graphene oxide precursor obtained by electrochemical treatment was washed with water and ultrasonicated for 12 min; the formed slurry was ball milled for 13 h at a ball milling speed of 300 r / min to obtain the product.
[0023] The products obtained in Example 1 and Comparative Example 1 were characterized by BET, with ball-milled fly ash as the benchmark. Figure 1 As shown, 1#, 2#, and 3# are the N2 adsorption and desorption isotherms of Example 1, Comparative Example 1, and ball-milled fly ash, respectively, and the specific surface areas are 73.4 m² / g, 301.4 m² / g, and 40.2 m² / g, respectively. Because the mass of fly ash is much greater than the mass of graphene oxide, in the fly ash-added ball-milled graphene oxide, the specific surface area of fly ash is substantially the same as that of fly ash ball-milled alone. The specific surface area of fly ash in fly ash ball-milled graphene oxide is 40.2 m² / g. The mass ratio of graphene oxide to fly ash in fly ash ball-milled graphene oxide is 1:10.
[0024] Specific surface area calculation formula: S, S1, and S2 are the specific surface area of the composite containing a single layer of graphene oxide (73.4 m² / g), the specific surface area of fly ash (40.2 m² / g), and the specific surface area of graphene oxide in the composite containing a single layer of graphene oxide, respectively; and are the mass of fly ash and the mass of graphene oxide, respectively; The specific surface area S2 of the graphene oxide in the composite containing a single-layer graphene oxide is calculated by the specific surface area calculation formula to be 404.5 m² / g. Compared with the specific surface area of the product of graphene oxide and deionized water ball milling of 301.4 m 2 / g, the specific surface area of the graphene oxide product after ball milling with fly ash increased by 34%. This is because fly ash reduces excessive damage to the graphene oxide sheets and provides binding sites for the peeled graphene oxide sheets, which shows that adding fly ash during ball milling helps to improve the monolayer rate and dispersion of graphene oxide.
[0025] Example 2 Concrete test blocks were prepared according to the mix ratio of 172 Kg of water, 330 Kg of cement, 798 Kg of sand, and 1100 Kg of crushed stone, to which cement-based material additives were added.
[0026] The preparation method of the cement-based material additive is as follows: after dissolving sodium rosin acid in water, mixing and stirring with the single-layer graphene oxide attached to the surface of the powder prepared in Example 1, adding silica sol after uniform mixing, to prepare the cement-based material additive. The mass ratio of sodium rosin acid, silica sol and graphene oxide is 8:4:1, and the addition ratio of graphene oxide is 0.05% of the mass of the cementitious material (cement).
[0027] Comparative Example 2 A benchmark concrete test block was prepared, and its mix ratio was the same as that of Example 2, except that no cement-based material additive was added.
[0028] Comparative Example 3 A concrete test block was prepared, and its mix ratio was the same as that of Example 2, except that only graphene oxide ball-milled with fly ash was added, and the addition ratio of graphene was 0.05% of the mass of the cementitious material (cement).
[0029] Comparative Example 4 A concrete test block was prepared, and its mix ratio was the same as that of Example 2, except that only separately ball-milled graphene oxide without fly ash was added, and the addition ratio of graphene was 0.05% of the mass of the cementitious material (cement).
[0030] Comparative Example 5 A concrete test block was prepared, and its mix ratio was the same as that of Example 2, except that only the air entraining agent sodium rosinate was added, and the addition ratio of the air entraining agent was 0.4% of the mass of the cementitious material (cement).
[0031] Comparative Example 6 A concrete test block was prepared, and its mix ratio was the same as that of Example 2, except that only the mixture of the air entraining agent sodium rosinate and the fly ash ball-milled graphene oxide was added.
[0032] When preparing the concrete test blocks in the above-mentioned Example 2 and Comparative Examples 2-6, the slump of the corresponding concrete was investigated, and the results are shown in Table 1: Table 1 Slump of concrete test blocks
[0033] Taking the concrete prepared in Comparative Example 2 as a benchmark, the slump of the concrete in Example 2 decreased slightly, but still maintained good fluidity. The slump in Comparative Example 3 is significantly lower than the benchmark, indicating that the use of fly ash ball-milled graphene oxide alone will reduce the fluidity of concrete. The slump of Comparative Example 4 is the lowest among all concretes. Compared with Comparative Example 3, it can be seen that adding fly ash when ball-milling graphene oxide can improve the adverse effect of the product on the fluidity of concrete. The slump in Comparative Example 5 is higher than that of the benchmark concrete, indicating that the addition of air-entraining agent can effectively improve the fluidity of concrete. The slump of Comparative Example 6 is higher than that of Comparative Example 3, indicating that the use of fly ash ball-milled graphene oxide and air-entraining agent at the same time can effectively improve the fluidity of concrete. In summary, the cement-based material additive used in this Example 2 can improve the fluidity of concrete to a certain extent, making it close to or reach the benchmark level, which shows that the cement-based material additive protected by the present invention has a positive effect on the fluidity of concrete.
[0034] The above concrete specimens were subjected to 3-day, 7-day and 28-day compressive strength tests (in MPa). The results are shown in Table 2.
[0035] Table 2 3d, 7d, 28d compressive strength of concrete specimens
[0036] As shown in Table 2, compared with the benchmark concrete in Comparative Example 2, the compressive strength of the concrete test block of Example 2 at 3 days, 7 days and 28 days is higher than that of the test blocks of all comparative examples, indicating that the cement-based material additive used in Example 2 has a significant effect on improving the compressive strength of concrete. The compressive strength of the concrete test block of Comparative Example 3 is higher than that of the test block of Comparative Example 2 at each test time point, which indicates that the graphene oxide ball-milled with fly ash helps to improve the compressive strength of concrete. The compressive strength of the test blocks prepared in Comparative Example 4 is higher than the benchmark but lower than that of Comparative Example 3, indicating that the addition of fly ash during ball milling helps to improve the reinforcing effect of graphene oxide on concrete. The compressive strength of the test blocks prepared in Comparative Example 5 is lower than the benchmark at all test time points, indicating that although the air entraining agent can improve the fluidity of concrete, it will have an adverse effect on the compressive strength of concrete. The performance of the test blocks prepared in Comparative Example 6 is close to that of Comparative Example 3 and higher than that of Comparative Example 5, indicating that the use of graphene oxide ball-milled with fly ash and air entraining agent at the same time can improve the compressive strength. In summary, the cement-based material additive used in Example 2 not only improves the fluidity of concrete, but also significantly improves the compressive strength of concrete at 3 days, 7 days and 28 days, showing the effectiveness of the additive in improving the comprehensive performance of concrete. At the same time, the graphene oxide ball-milled from fly ash also has a positive effect on the compressive strength of concrete, while the use of graphene oxide alone has a relatively limited enhancement, and the addition of air entraining agent alone has a negative effect on the strength.
[0037] The above concrete test blocks were subjected to an anti-permeability test, and the average water seepage height (mm) is shown in Table 3 below.
[0038] Table 3 Average water seepage height
[0039] As can be seen from the above table, the concrete test block of Example 2 has the lowest average water seepage height, which is much lower than the test blocks of all comparative examples, which shows that the cement-based material additive used in Example 2 significantly improves the impermeability of concrete. The average water seepage height of Comparative Example 3 is lower than that of Comparative Example 2, indicating that the graphene oxide ball-milled with fly ash helps to improve the impermeability of concrete. The average water seepage height of Comparative Example 4 is lower than the benchmark, but higher than that of Example 2 and Comparative Example 3, indicating that the use of graphene oxide alone can also improve the impermeability of concrete to a certain extent, but the effect is not as good as that of graphene oxide ball-milled with fly ash. The average water seepage height of Comparative Example 5 is lower than the benchmark, indicating that the addition of air entraining agent helps to improve the impermeability of concrete. The average water seepage height of Comparative Example 6 is lower than the benchmark, indicating that the use of graphene oxide ball-milled with fly ash and air entraining agent at the same time can improve the impermeability. In summary, the cement-based material additive used in Example 2 significantly improves the impermeability of concrete, making it the best performer among all test blocks. In addition, the addition of fly ash ball-milled graphene oxide and air-entraining agent can also improve the impermeability of concrete to a certain extent, but the effects vary.
[0040] The freeze-thaw resistance test was carried out on the above concrete test blocks, and the results are shown in Table 4: Table 4 Concrete mass loss rate after freeze-thaw cycles (%):
[0041] The results show that the concrete in Comparative Example 2 has a mass loss rate of 4.95% after 150 freeze-thaw tests, and it has exceeded 5% at 160 times (data not shown). In Comparative Example 3, the addition of fly ash ball-milled graphene oxide can improve the freeze-thaw resistance of concrete, but the effect is not as obvious as the use of air-entraining agent in Comparative Example 5. Comparative Example 4 uses graphene oxide without fly ash during ball milling, and the mass loss rate is close to 5% after 300 freeze-thaw tests, and the freeze-thaw resistance barely reaches F300. In Comparative Example 6, fly ash ball-milled graphene oxide and air-entraining agent are used at the same time, and the freeze-thaw resistance is significantly improved. The cement-based material additive added in Example 2 contains graphene oxide ball-milled with fly ash, air-entraining agent and water-soluble filler at the same time, and the freeze-thaw resistance is improved.
[0042] The above experiments verified that the composite formed by attaching a single layer of graphene to the surface of the powder is compounded with an air entraining agent and a water-soluble filler and added to cement-based materials as an additive, which can improve the workability, compressive strength, impermeability and freeze-thaw resistance of the concrete specimens.
[0043] Therefore, the present invention relates to a composite containing a single-layer graphene oxide, and a preparation method and application thereof. Building material powder is added during the ball milling process of a graphene oxide precursor, and the obtained composite is a composite formed by the single-layer graphene attached to the surface of the powder, so that its dispersibility in concrete is improved; the composite is compounded with an air entraining agent and a water-soluble filler and then added to a cement-based material as an additive, which can improve the performance of the cement-based material.
[0044] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a composite containing a single-layer graphene oxide, characterized in that: Here are the steps: The graphene oxide precursor is washed with water and ultrasonicated, the formed slurry is ball-milled, and building material powder is added during the ball-milling process to obtain a composite formed by a single layer of graphene attached to the surface of the powder.
2. The method for preparing a composite containing a single-layer graphene oxide according to claim 1, characterized in that: The building material powder is one of fly ash, recycled aggregate and slag powder.
3. The method for preparing a composite containing a single-layer graphene oxide according to claim 2, characterized in that: In the composite, the mass ratio of graphene oxide to building material powder is 5:1-50:
1.
4. A composite containing a single layer of graphene oxide, characterized in that: The compound is prepared by the preparation method described in any one of claims 1 to 3.
5. An application of a composite containing a single layer of graphene oxide, characterized in that: The composite prepared according to claim 4 is used as an additive in cement-based materials.
6. The use of a composite containing a single-layer graphene oxide according to claim 5, characterized in that: The additives also include air entraining agents and water-soluble fillers.
7. The use of a composite containing a single-layer graphene oxide according to claim 6, characterized in that: The preparation steps of the additive are: adding a composite containing a single-layer graphene oxide to an aqueous solution of an air entraining agent, stirring evenly, and then adding a water-soluble filler to obtain an additive for a cement-based material; Alternatively, an air entraining agent and a water-soluble filler are added during the ball milling process of preparing a composite containing a single-layer graphene oxide, and finally an additive for a cement-based material is obtained.
8. The use of a composite containing a single-layer graphene oxide according to claim 7, characterized in that: In the additive of the cement-based material, the mass ratio of the air entraining agent to the graphene oxide is 5:1-50:1, and the ratio of the water-soluble filler to the graphene oxide is 2:1-20:
1.
9. The use of a composite containing a single-layer graphene oxide according to claim 8, characterized in that: The air entraining agent is an anionic surfactant, and is one of sodium rosin acid, modified rosin sulfonate, alkyl sulfonic acid / sulfate, and fatty acid salt; the water-soluble filler is silica sol.